Volume 9: Oil and Gas Applications; Supercritical CO2 Power Cycles; Wind Energy 2017
DOI: 10.1115/gt2017-63643
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of a NACA 0021 Airfoil Section Through 180-Degree Angle of Attack at Low Reynolds Numbers for Use in Wind Turbine Analysis

Abstract: Wind turbine industry has a special need for accurate post stall airfoil data. While literature often covers incidence ranges [−10deg,+25deg] smaller machines experience a range of up to 90 deg for horizontal axis and up to 360 deg for vertical axis wind turbines (VAWTs). The post stall data of airfoils is crucial to improve the prediction of the start-up behavior as well as the performance at low tip speed ratios. The present paper analyzes and discusses the performance of the symmetrical NACA 0021 airfoil at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Within the limit of the resolution provided by the finite number of pressure tappings, the laminar separation bubble can be identified at around 0.1 c ~0.2 c for θ = 35 ° and θ = 45 ° (see Figure ). It must be noted that at θ = 45 ° , the theoretical incidence angle is about α = 30 ° , which is already far beyond the static stall angle of ~13 ° (NACA0021) at similar Reynolds numbers . Even taking the curvature effect into consideration, the dynamic stall effect that significantly delays the stall angle is successfully captured in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the limit of the resolution provided by the finite number of pressure tappings, the laminar separation bubble can be identified at around 0.1 c ~0.2 c for θ = 35 ° and θ = 45 ° (see Figure ). It must be noted that at θ = 45 ° , the theoretical incidence angle is about α = 30 ° , which is already far beyond the static stall angle of ~13 ° (NACA0021) at similar Reynolds numbers . Even taking the curvature effect into consideration, the dynamic stall effect that significantly delays the stall angle is successfully captured in this study.…”
Section: Resultsmentioning
confidence: 99%
“…It must be noted that at θ = 45°, the theoretical incidence angle is about α = 30°, which is already far beyond the static stall angle of~13°(NACA0021) at similar Reynolds numbers. 43,44 Even taking the curvature effect into consideration, the dynamic stall effect that significantly delays the stall angle is successfully captured in this study. The laminar separation bubble bursts when the blade reaches about θ = 50°F (note: Since at this low tip speed ratio, the blade will experience all possible incidence angle from α = −180°to α = 180°; the radius axis for incidence angle data is significantly larger than that for torque coefficient data.…”
Section: On-board Pressure Measurement Data Interpolationmentioning
confidence: 95%
“…The first and second stall of the static polars, as well as their according hysteresis, are known to literature. Holst et al [1] showed a hysteresis loop at the very high angles in a full range investigation between 0 and 180 deg. This loop is also visible in the full range static polars shown in figs.…”
Section: Lift Under Dynamic Aoa Changes In Deep Stallmentioning
confidence: 96%
“…There are studies of symmetric airfoils that investigate thinner airfoils like the NACA 0012 [12,13] and NACA 0015 [13,14], but data of thicker airfoils, especially at lower Reynolds numbers, are rare. There are experimental studies of a NACA 0018 airfoil done by Rainbird et al [15,16] and Du et al [17,18] but the present study investigates the NACA 0021, providing additional data referring to the existing work of Holst et al [1,19]. This paper concentrates on experiments with dynamic AoA changes at two different Reynolds numbers of Re = 140 k and 180 k.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation